On-Chip DO sensor based on phosphorescence lifetime spectroscopy for investigation of activation parameters in photodynamic therapy of cancers - E. Heydari; S. Delavari; K. Hajisharifi; S. Emadi; H. Radnaseri; M. Moeini; H. Mehdian; A. Erdem; G. Bai; M. Razzaghi (Sensing and Bio-Sensing Research)
A 3D-printed optofluidic chip with an embedded dissolved oxygen sensor, empowered with a time-resolved phosphorescence lifetime spectroscopy platform, is developed for indirect analysis of reactive oxygen species (ROS) dynamics in photodynamic therapy (PDT). This platform is implemented for continuous evaluation of ROS production/elimination through real-time measurement of photoluminescence (PL) lifetime (τ) during PDT treatment, revealing the key contributions of the photosensitizer (PS), excitation laser, and the medium in ROS generation during this process. Rose Bengal (RB) is utilized as a PS to demonstrate this system's capability to analyze and tune the PS activation parameters such as PS concentration, laser exposure time, and power. In addition, the platform provides important information on the medium activation duration, the maximum changes in the PL lifetime (∆τmax), and the time to reach ∆τmax. For the Dulbecco's modified eagle medium high glucose (DMEM HG) containing fetal bovine serum (FBS), RB, and A375 human melanoma cell line as a representative example, these parameters are 1070 s, 4.4 μs, and 780 s respectively. Two ROS scavengers of sodium pyruvate (SP) and terephthalic acid (TA) are used to demonstrate that more than 90 % of the change in the τ corresponds to OH• and H2O2 radicals, confirming the correlation between ROS generation/elimination and τ variations. Moreover, this system is compared with conventional absorption and photoluminescent methods based on 1,3-diphenylisobenzofuran (DPBF) indicator. Unlike DPBF and similar indicators, this on-chip system besides providing real-time data on the dynamics of activation and deactivation of the PSs, enables distinguishing the contribution of various parameters, and is not consumed during the measurement and can be reused multiple times. Therefore, the developed platform is potentially beneficial for on-chip drug analysis and development in PDT therapy, as well as other biomedical applications.